2015
DOI: 10.1002/jssc.201500115
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-modified organic-silica hybrid monolithic column for mixed-mode per aqueous and ion-exchange capillary electrochromatography

Abstract: A novel organic-silica hybrid monolith was prepared through the binding of histidine onto the surface of monolithic matrix for mixed-mode per aqueous and ion-exchange capillary electrochromatography. The imidazolium and amino groups on the surface of the monolithic stationary phase were used to generate an anodic electro-osmotic flow as well as to provide electrostatic interaction sites for the charged compounds at low pH. Typical per aqueous chromatographic behavior was observed in water-rich mobile phases. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Previous reports described the successful use of sodium 1‐heptanesulfonate as ion‐pairing agent for the separation of many drugs . Due to the ionizable nature of free amino acids (cationic, anionic or even zwitterionic), their separation can also be achieved by ion‐exchange or ion‐pair RP HPLC . In ion‐pair RP HPLC, the separation of amino acid ionic compounds can be improved by adding ion‐pairing reagents to the mobile phase, which can enhance their retention.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports described the successful use of sodium 1‐heptanesulfonate as ion‐pairing agent for the separation of many drugs . Due to the ionizable nature of free amino acids (cationic, anionic or even zwitterionic), their separation can also be achieved by ion‐exchange or ion‐pair RP HPLC . In ion‐pair RP HPLC, the separation of amino acid ionic compounds can be improved by adding ion‐pairing reagents to the mobile phase, which can enhance their retention.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that a mixture of toluene, DMF, acrylamide, and thiourea was baseline separated successfully with good peak shapes under the mobile phase of 80% (v/v) ACN/HAc–NaAc (Fig. A), and they were eluted according to their polarity in order from low to high, which was consistent with the hydrophilic interaction (HI) mechanism . The effect of ACN content on the retention factors ( k´ ) was investigated by using different ACN contents from 50 to 90% (v/v) in the mobile phase.…”
Section: Resultsmentioning
confidence: 64%
“…Rapid developments have been noticed with mixed‐mode organic–silica monoliths as they allow for more than one kind of separation capability using one single column. Among these are columns prepared from TMOS and 3‐chloropopyltrimethoxysilane (CPTMS) functionalized by nucleophilic substitution reactions with tertiary amines such as 4,5‐imidazoledicarboxylic acid , imidazole‐1‐acetic acid , 4,4’‐dipyridyl , o ‐phenanthroline , or histidine . For analysis of wide range of compounds these columns exhibited multiple retention mechanisms such as hydrophobic, hydrophilic, π–π and ion‐exchange interactions in reversed‐phase and per aqueous CEC.…”
Section: Organic–silica Hybrid Monolithsmentioning
confidence: 99%